Potentially bioavailable iron produced through benthic cycling in glaciated Arctic fjords of Svalbard - Katja Laufer-Meiser (Nature Portfolio, 2021)
The impacts of a melting Arctic on the biogeochemistry of marine ecosystems are unknown. Here, the authors investigate glacial input of iron to Svalbard fjords finding that reworking of glacial iron in fjord sediment is important to make iron bioavailable, but could be susceptible to glacial retreat.